Perception of Leadership in the Implementation of Organizational Strategies Before Covid-19 in Technological Higher Secondary Education Schools - Ramírez-Sánchez, Verónica (2023)
Objective. This work aimed to identify the effect of transformational and transactional leadership in the design and implementation of organizational strategies during the COVID-19 pandemic. Method. The study used a quantitative methodology with a non-experimental cross-sectional design; the scope was descriptive and correlational. The instruments were applied to 294 workers from six technological higher secondary education institutions in Tabasco, Mexico. Results. Significant correlations were found between transformational and transactional leadership related to the design and implementation of strategies carried out in these educational institutions. Another finding was that sociodemographic characteristics, such as gender, marital status, and job seniority, do not influence the levels of perception of the design or implementation of organizational strategies. Conclusions. It is concluded that leadership styles in the institution are related to and influence the design and implementation of the proposed strategies.